Menyoal Wacana Perluasan Waktu Haji (Studi Kritis atas Pemikiran MasdarFarid Mas’udi) - Muhammad Hariyadi; Adib Minanul Cholik (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2018)
This article criticizes Masdar Faried Masudi’s viewed that the implementation of the pilgrimage should not be done only once, ie 9 to 13 Dzulhijjah, but can be implemented for several times within a three-month span. The view is based on the many difficulties (masyaqqah) and several tragedies that occur during the Haj season because Muslims around the world run wukuf and throw jumrah at the same time and time. The argument proposed by Masdar is the timing of the three-month pilgrimage time and the coincidence of the implementation of the pilgrimage of the Messenger of Allah (peace and blessings of Allah be upon him) which coincided with the 9th Dzulhijjah. After the author conducted an analysis of the hadiths of the Prophet about the pilgrimage, the Prophet’s statement that Hajj was the Arafah, not a coincidence but was one of the provision of Hajj, so that anyone who performs Hajj must be present at Arafah, otherwise the Haj is not valid. Attendance on Arafah also became consessus of agreement among the scholars. Second, the three-month period is indeed an area of ijtihad. Meanwhile the views of the scholars on the specificity of the Hajj on September 9-13, in addition to the direct practice of the Prophet, are also the takhsis (specifity) of the context of the pilgrimage towards the general perspective of Qur’an, thus having a reasoned consideration rational and theological that become stronger than just a scholar’s ijtihad (independent exertion of jurist in finding solutions)